Activation markers in Behçet's disease. - Coskun, Basak; Saral, Yunus; Gödekmerdan, Ahmet; Erden, Ilker; Coskun, Naci (My University, 2005)
INTRODUCTION: One of the main problems in Behçet's disease is the lack of an original laboratory marker that can reflect clinical activity. In this study, laboratory parameters that could be used as indicators of active disease are investigated. MATERIALS AND METHODS: The study included a total of 40 patients with Behçet's disease, 25 of whom were active and 15 inactive, who applied to Firat University, Firat Medical Center Dermatology, Rheumatology, Physiotherapy, and Ophthalmology outpatient clinics and a control group composed of 30 healthy volunteers. Serum neopterin, C-reactive protein (CRP), and sedimentation rate (ESR) levels were determined in all patients and healthy controls. RESULTS: Serum neopterin, CRP, and ESR levels in active Behçet's disease patients were significantly higher than those in both the inactive group and healthy controls (p<0.001). CONCLUSIONS: It was contemplated that together with serum CRP and ESR, neopterin could be a useful laboratory parameter in patients in whom disease activation could not be determined.
Keywords: Adult; Behcet Syndrome; Biological Markers; Blood Sedimentation; C-Reactive Protein; Case-Control Studies; Female; Humans; Male; Neopterin; Predictive Value of Tests; biological marker; C reactive protein; neopterin; MLCS; MLOWN; adult; article; Behcet disease; blood; case control study; erythrocyte sedimentation rate; evaluation; female; human; male; metabolism; prediction and forecasting